High-precision immune-related plasma proteomics profiling predicts response to immunotherapy in patients with triple-negative breast cancer - Yuling Xiao; Hang Zhang; Yi Xiao; Ying Wang; Jing Zhang; Qi Hua; Pengchen Hu; Xinyan Lyu; Weihua Shou; Xin Hu; Zhiming Shao; Yizhou Jiang; et al. (Cancer Biology & Medicine)
Objective: While immunotherapy holds great potential for triple-negative breast cancer (TNBC), the lack of non-invasive biomarkers to identify beneficiaries limits the application. Methods: Paired baseline, on-treatment, and post-treatment plasma samples were collected from 195 TNBC patients receiving anti-PD-1 immunotherapy in this retrospective study conducted at the Fudan University Shanghai Cancer Center (FUSCC) for sequential high-precision proteomic profiling. Results: ARG1, NOS3, and CD28 were identified as plasma proteins significantly associated with the response to immunotherapy in neoadjuvant settings or in advanced stages of TNBC. Matched single-cell RNA sequencing data were incorporated to correlate peripheral plasma with the tumor microenvironment. Furthermore, the Plasma Immuno Prediction Score was developed to demonstrate significant predictive power for evaluating the efficacy and prognosis of patients undergoing neoadjuvant immunotherapy. Conclusions: The results underscore the importance of systemic immunity in the immunotherapy response and support the use of plasma protein profiles as a feasible tool for enhancing personalized management of immunotherapy in breast cancer.